Audit committee strength and auditors' risk assessments: The moderating role of CEO narcissism. Issue 3 (30th June 2021) - Zengin‐Karaibrahimoglu, Yasemin; Emanuels, Jim; Gold, Anna; Wallage, Philip
Abstract : This paper examines the impact of two elements of the client's control environment on auditor's assessment of the risk of material misstatement: audit committee strength and CEO narcissism, the latter of which is a component of management philosophy, operating style, and tone at the top. We predict and find that auditors' risk assessments are adequately responsive to both elements; however, importantly, a strong audit committee decreases perceived risk assessments only when the client has a CEO with less narcissistic characteristics. In other words, our findings suggest that the presence of narcissistic CEOs' attitudes weakens the perceived audit committee effectiveness, leading auditors to rely less on a strong audit committee. Our findings contribute to the auditing literature by exploring auditors' responses to the complex dynamics between management boards and those charged with governance. From a practical perspective, our results suggest that auditing standards and practice guidance should consider making such complexities and the role of management attitudes and styles even more explicit.